Alkali catalysed transesterification of rapeseed oil - Vávra, Aleš (Univerzita Pardubice, 2019)
The subject of this thesis was a study of the preparation of ester with a low content of free fatty acids by alkali catalysed transesterification. The transesterification of rapeseed oil was carried out under homogeneous catalyst (batch reactor) and heterogeneous catalyst (fixed bed reactor). For the homogeneous catalysis (potassium hydroxide), the attention was paid to (i) the monitoring of transesterification by pH and conductivity, (ii) the preparation of esters with a low content of free fatty acids by two methods: one method is purifying the esters with a high content of free fatty acids by adding calcium hydroxide and second method is stopping of reaction by addition of inorganic acids, (iii) the detailed description of side product of transesterification (the glycerol phase), including ester losses after separation of the ester phase from the glycerol phase. Butanol as another alcohol, which is possible to use in transesterification of rapeseed oil, was used and the transesterification including the various types of stopping reaction and separation of products were described. The obtained data were statistically evaluated in programs STATISTICA and QC Expert. In the case of the heterogeneous catalysis, the possibility of using mixed oxides in a fixed-bed reactor was studied. Two types of mixed oxides (Mg-Al and Mg-Fe) were used in the transesterification with methanol and obtained results were compared. Moreover, the long-term catalyst test (300 h) was carried out to study the stability of mixed oxides.
Alkalicky katalyzována transesterifikace řepkového oleje
Keywords: transesterifikace; alkalicky katalyzátor; volné mastné kyseliny; estery; transesterification; alkali catalyst; free fatty acids; esters